Quantifying Airborne Dispersal Route of Corynespora cassiicola in Greenhouses - Zhao, Qian; Shi, Yanxia; Wang, Yuhong; Xie, Xuewen; Li, Lei; Guo, Liyun; Chai, Ali; Li, Baoju (Frontiers in Microbiology, 2021)
Target leaf spot (TLS), caused by Corynespora cassiicola, is an emerging and high-incidence disease that has spread rapidly on the global scale. Aerospores released by infected plants play a significant role in the epidemiology of cucumber TLS disease; however, no data exist concerning the infectiousness and particle size of C. cassiicola aerospores, and the experimental evidence for the aerospores transmission was lacking. In the present study, highly effective approaches to collect and quantify aerospores were developed for exposure chamber and greenhouse studies. Quantifiable levels of C. cassiicola aerospores were detected in 27 air samples from nine naturally infested greenhouses, ranging from 198 to 5969 spores/m3. The C. cassiicola strains isolated from air samples were infective to healthy cucumber plants. Exposure chambers were constructed to study the characteristics of C. cassiicola aerospores released by artificially infested cucumber plants. The particle size of C. cassiicola ranged predominately from 2.1 to 4.7 μm, accounting for 71.97% of the total amount. In addition, the transmission dynamics of C. cassiicola aerospores from donor cucumber plants to recipient cucumber plants were confirmed in exposure chambers and greenhouses. The concentration of C. cassiicola aerospores was positively associated with cucumber TLS disease severity. This study suggested that aerospore dispersal is an important route for the epidemiology of plant fungal disease, and these data will contribute to the development of new strategies for the effective alleviation and control of plant diseases.